2021
DOI: 10.1093/cercor/bhab304
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal Representations of Event Structure and Temporal Context during Episodic Temporal Order Memory

Abstract: The hippocampus plays an important role in representing spatial locations and sequences and in transforming representations. How these representational structures and operations support memory for the temporal order of random items is still poorly understood. We addressed this question by leveraging the method of loci, a powerful mnemonic strategy for temporal order memory that particularly recruits hippocampus-dependent computations of spatial locations and associations. Applying representational similarity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 82 publications
0
18
0
Order By: Relevance
“…or close in narrated, but not actual, time (Bellmund et al, 2022; but see Deuker et al, 2016). Additional studies have reported decreased similarity in CA3/DG between objects that share spatiotemporal context (Copara et al, 2014; Dimsdale-Zucker et al, 2018; Kyle, Smuda, et al, 2015; Liu et al, 2022), and specifically in DG (Berron et al, 2016; see also Baker et al, 2016). Our results extend this prior work in two critical ways: first, we show that DG pattern separation can occur in the temporal domain, thus advancing our knowledge of how temporally extended experiences are represented in the brain (Davachi & DuBrow, 2015; Eichenbaum, 2014).…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…or close in narrated, but not actual, time (Bellmund et al, 2022; but see Deuker et al, 2016). Additional studies have reported decreased similarity in CA3/DG between objects that share spatiotemporal context (Copara et al, 2014; Dimsdale-Zucker et al, 2018; Kyle, Smuda, et al, 2015; Liu et al, 2022), and specifically in DG (Berron et al, 2016; see also Baker et al, 2016). Our results extend this prior work in two critical ways: first, we show that DG pattern separation can occur in the temporal domain, thus advancing our knowledge of how temporally extended experiences are represented in the brain (Davachi & DuBrow, 2015; Eichenbaum, 2014).…”
Section: Discussionmentioning
confidence: 96%
“…Putatively higher similarity at the boundary could reflect prediction of the coming event (Brown et al, 2016; Hindy et al, 2016; Kok & Turk-Browne, 2018; Schapiro et al, 2012), accompanied by reactivation at the end of the event (Ben-yakov & Dudai, 2011; Cohn-Sheehy et al, 2021; Griffiths & Fuentemilla, 2020; Silva et al, 2019; Sols et al, 2017). One speculation is that there is a shift in hippocampal sequence representations through learning (Ben-yakov et al, 2014; Davachi & DuBrow, 2015), whereby contextual stability during initial learning promote similarity of event representations (DuBrow & Davachi, 2014; Hasselmo & Eichenbaum, 2005; Manns et al, 2007), and these similar representations later facilitate reactivation of learned event components through pattern completion (Grande et al, 2019; Horner et al, 2015; Liu et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations